A Review of Duloxetine 60 mg Once‐Daily Dosing for the Management of Diabetic Peripheral Neuropathic Pain, Fibromyalgia, and Chronic Musculoskeletal Pain Due to Chronic Osteoarthritis Pain and Low Back Pain. Issue 3 (21st June 2012) - Pergolizzi, Joseph V.; Raffa, Robert B.; Taylor, Robert; Rodriguez, Gabriel; Nalamachu, Srinivas; Langley, Paul
Abstract Background: Duloxetine is a selective dual neuronal serotonin (5‐Hydroxytryptamine, 5‐HT) and norepinephrine reuptake inhibitor (SSNRI). It is indicated in the United States for treatment of major depressive disorder (MDD), generalized anxiety disorder (GAD), and several chronic pain conditions, including management of diabetic peripheral neuropathic pain, fibromyalgia, and chronic musculoskeletal pain due to chronic osteoarthritis (OA) pain and chronic low back pain (LBP). Its use for antidepressant and anxiolytic actions has been extensively reviewed previously. We here review the evidence for the efficacy of 60 mg once‐daily dosing of duloxetine for chronic pain conditions. Method: The literature was searched for clinical trials in humans conducted in the past 10 years involving duloxetine. Results: There were 199 results in the initial search. Studies not in the English language were excluded. We then included only studies of diabetic peripheral neuropathic pain, fibromyalgia, and chronic musculoskeletal pain (OA and LBP). Studies of painful symptoms reported in mental health studies were excluded. This resulted in 32 studies. Articles that did not include a 60 mg/day daily dose as a study arm were excluded. This resulted in 30 studies, broken down as follows: 12 for diabetic peripheral neuropathy, 9 for fibromyalgia, 6 for LBP, and 3 for OA pain. Conclusions: The studies reviewed report that duloxetine 60 mg once‐daily dosing is an effective option for the management of diabetic peripheral neuropathic pain, fibromyalgia, and chronic musculoskeletal pain due to chronic OA pain and chronic LBP. As these pains are often comorbid with MDD or GAD, duloxetine might possess the pharmacologic properties to be a versatile agent able to address several symptoms in these patients. With adequate attention to FDA prescribing guidance regarding safety and drug–drug interactions, duloxetine 60 mg once‐daily dosing appears to be an effective option in the appropriate pain patient population.